2015
DOI: 10.1007/s00167-015-3582-z
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction; is a tourniquet necessary? A randomized controlled trial

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…Finally, 16 studies published from 1982 to 2015 fulfilled the selection criteria and were included in the systematic review and meta-analysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The included articles did not provide any additional studies to evaluate, and detailed study selection process is shown in ►Fig. 2.…”
Section: Results Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 16 studies published from 1982 to 2015 fulfilled the selection criteria and were included in the systematic review and meta-analysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The included articles did not provide any additional studies to evaluate, and detailed study selection process is shown in ►Fig. 2.…”
Section: Results Study Selectionmentioning
confidence: 99%
“…Five RCTs conducted by Arciero et al [13][14][15][16][17] included patients who underwent ACL reconstruction and another five studies [19][20][21][22]27 assessed the effect of tourniquet in patients with arthroscopic meniscectomy. The remaining six studies 18,[23][24][25][26]28 recruited patients who underwent knee arthroscopic surgery without cruciate ligament reconstruction, meniscus repairment, and other complex knee arthroscopic procedures.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it will prevent tourniquetassociated immediate postoperative pain and haemarthrosis. 12 Some studies showed that the arthroscopic ACLR can be carried out effectively without the use of tourniquet and use of tourniquet does not add any extra benefit when compared with non-tourniquet arthroscopic knee surgeries. 13,14 In our study, majority (97.9%) use tourniquet during the surgery out of which 6.3% does not advise it during graft harvest.…”
Section: Tourniquetmentioning
confidence: 99%